AB0469 THE EFFECTS OF ACUPUNCTURE ON XEROSTOMIA, XEROPHTHALMIA AND ANTIBODY MODIFICATION IN PATIENTS WITH SJŐGREN SYNDROME: A META-ANALYSIS. (June 2019) - Li, Tzu-Hao; Kung, Yen-Ying; Tsai, Chang-Youh
Abstract : Background: Xerostomia and xerophthalmia are common chief complaints among patients with Sjőgren syndrome (SS) but there has been no satisfying pharmacy to relieve the associated symptoms; hence the effectiveness of other non-pharmacological interventions such as acupuncture should be accessed. Objectives: To access the therapeutic effects of acupuncture on xerostomia and xerophthalmia in patient with SS. Methods: We conducted a meta-analysis of randomized clinical trials (RCTs) which evaluated the effectiveness of xerostomia and xerophthalmia in SS. PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Chongqing Weipu Database (CQVIP), China Academic Journals Full-text Database, AiritiLibrary, Chinese Electronic Periodicals Service (CEPS), China National Knowledge Infrastructure (CNKI) Database were searches through Oct, 2018 to select studies. Data for evaluation of subjective and objective xerostomia was extracted and was assessed with random-effects meta-analysis. Results: After searching, a total of 680 references were yielded and five RCTs were included, covering 460 patients dry mouth resulted from SS, among whom 229 patients received acupuncture and 231 patients were control group. Acupuncture group was associated with higher subjective response rate (odds ratio 3.036, 95% confidence interval [CI] 1.828 – 5.042, P < 0.001, Fig. 1) and increased salivary flow rate (weighted mean difference [WMD] 3.066, 95% CI 2.969 – 3.164, P < 0.001, Fig. 2), as an objective marker. Regarding xerophthalmia, acupuncture group revealed less dry eye visual analog scale (VAS, WMD -1.035, 95% CI -1.457 - -1.673, P < 0.001, Fig. 3), better Schirmer test (WMD 2.357, 95% CI 1.021 – 3.692, P = 0.001, Fig. 4) and trend of longer break-up time (WMD 4.927, 95% CI -0.055 – 9.908, P = 0.053, Fig. 5). In addition, two studies examined IgG levels, which were lower in the acupuncture group (WMD -166.857, 95% CI -233.138 - -100.576, P < 0.001, Fig. 6). Conclusion: In the present meta-analysis, acupuncture improves both subjective and objective markers of xerostomia and xerophthalmia in patients with SS and is considered as an option of non-pharmacological treatment. References: [1] Vivino FB. Sjogren's syndrome: Clinical aspects. Clin Immunol. 2017;182:48-54. [2] Kuklinski E, Asbell PA. Sjogren's syndrome from the perspective of ophthalmology. Clin Immunol. 2017;182:55-61. Disclosure of Interests: None declared